2020
DOI: 10.1038/s41467-020-20031-4
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus VLT-ORF63 fusion transcript induces broad viral gene expression during reactivation from neuronal latency

Abstract: Varicella-zoster virus (VZV) establishes lifelong neuronal latency in most humans world-wide, reactivating in one-third to cause herpes zoster and occasionally chronic pain. How VZV establishes, maintains and reactivates from latency is largely unknown. VZV transcription during latency is restricted to the latency-associated transcript (VLT) and RNA 63 (encoding ORF63) in naturally VZV-infected human trigeminal ganglia (TG). While significantly more abundant, VLT levels positively correlated with RNA 63 sugges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 47 publications
1
46
1
Order By: Relevance
“…The mechanisms leading to latency and subsequent reactivation are still to be unraveled. However, a recent study has suggested VLT-ORF63 transcripts from VZV as potential inducers of reactivation (282). In addition, cellmediated immunity appears to play an important role in the immune response to VZV and also latency (283)(284)(285).…”
Section: Varicella Zoster Virusmentioning
confidence: 99%
“…The mechanisms leading to latency and subsequent reactivation are still to be unraveled. However, a recent study has suggested VLT-ORF63 transcripts from VZV as potential inducers of reactivation (282). In addition, cellmediated immunity appears to play an important role in the immune response to VZV and also latency (283)(284)(285).…”
Section: Varicella Zoster Virusmentioning
confidence: 99%
“…However, pORF63 did not induce the transcription of any IE, early or late gene, except for the IE promiscuous transactivator pORF61 and the early (E) transcript RNA 16-1 ( Moriuchi et al, 1993 ). These results indicated that gene transcription during VZV reactivation is initiated through VLT-ORF63 transcription/pVLT-ORF63 translation ( Ouwendijk et al, 2020 ). However, whether VLT and ORF63 RNA transcripts are produced by the same or distinct populations of neurons remains unclear, as human TG are composed of dissimilar subtypes of neurons, and how these transcripts may affect ability of VZV to reactivate from latent in neurons is unknown ( Depledge et al, 2018b ).…”
Section: Roles Of Icp22/orf63 In Viral Latency and Reactivationmentioning
confidence: 98%
“…Although the expression levels were different, the expression levels of VLT and ORF63 transcripts were significantly correlated, suggesting that they coregulate expression during latent VZV infection ( Ouwendijk et al, 2012 ; Depledge et al, 2018a ). This apparent expression of two distinct viral transcripts during latency is unique among well-studied α-herpesviruses, suggesting that these two transcripts and/or their encoded proteins play an important role in the latency and reactivation of VZV ( Ouwendijk et al, 2020 ). In the human induced pluripotent stem cell–derived sensory neuron (HSN) latency model in vitro , the results of coexpression of VLT and two VLT-ORF63 fusion products, VLT63-1 and VLT63-2, showed that the encoded pVLT-ORF63 fusion protein can act as an initiator of VZV reactivation in infected human TG, providing new insights into the mechanism by which VZV establishes latency and reactivation ( Ouwendijk et al, 2020 ).…”
Section: Roles Of Icp22/orf63 In Viral Latency and Reactivationmentioning
confidence: 99%
See 2 more Smart Citations